PENERAPAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) UNTUK PENGEMBANGAN KOSAKATA ENGLISH FOR BUSINESS - Iksan, Iksan (Institut Agama Islam Negeri (IAIN) Bone, 2017)
This research is a classroom action research that aims to improve the students’ ability in recognizing, understanding, and using vocabularies in English for Business, and enhance the quality of learning process from teacher or students view through the implementation of NHT. The source of research data was from the learning process of English subject to the students X grade of SMA Negeri 18 Makassar. The result showed that the activities of students become very pleased and increase their learning vocabulary English for Business by applying NHT in the class